Inhibition of salty taste and sodium appetite by estrogens in spontaneously hypertensive rats - Pereira, Emilson Donizete; Zenatti, Aline Aparecida; Menani, José Vanderlei; De Luca, Laurival Antonio; Andrade, Carina A. F. (Frontiers in Physiology, 2023)
Estrogens have a well-known effect to reduce salt intake in rats. Few studies have focused on the role of sex hormones such as estradiol in sodium palatability in normotensive and hypertensive humans and animals. This mini review focuses on recent findings about estradiol interaction with brain angiotensin II to control sodium palatability that results from sodium appetite in spontaneously hypertensive rats.